(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
This issue of Libellarium features papers based on the presentations from the 2ndPublishing trends and contexts conference which took place in Pula, Croatia, on 8-9 December 2014. All papers were subject to evaluation and classification by two independent reviewers, according to the journal’s editorial policy. The conference gathered a group of experts from prominent European universities from England, France, Germany, Lithuania, Netherlands, Poland, Scotland, Sweden, Slovenia and Croatia–the details are available on the conference web site: http://epubconf.unizd.hr/hr/index.php. The papers published in this volume concentrate on four main problems: new possibilities for publishers, booksellers and authors caused by the introduction of digital technologies in the publishing processes, models used in the digital environment, teaching publishing at the university level, and finally, the status of publishing studies as an emerging scholarly discipline. The first part features five papers. Tom D. Wilson in E-books: the publishers’ dilemma reports on a study of publishers’ attitudes towards e-books in three countries: Sweden, Lithuania and Croatia, showing a great contrast between the rise of the e-book in English speaking countries and those of small languages. Elena Maceviciute, Birgitta Wallin and Kersti Nilsson (Book selling and e-books in Sweden) address the issue of the understanding of the book-selling situation in Sweden, by answering three crucial questions: how Swedish booksellers see the impact of e-books on their business, how and why they adopt and develop e-book sales, and what they perceive as barriers to e-book selling. Interestingly, the results have shown that the Swedish booksellers do not feel their business is threatened by e-books. In E-book aggregators: new services in electronic publishing Tomislav Jakopec investigates e-book aggregators as new services in electronic publishing, showing that e-book aggregation exists as a business model and that its further development will show the extent to which it is sustainable. Arūnas Gudinavičius (Is self-publishing a salvation for authors? The case of Lithuanian printed bestseller in the digital environment) deals with the possibilities of self-publishing, taking a case from a small language market (Andrius Tapinas’ book Hour of the Wolf) and analyzing the attempts of the author to translate it into English and sell it through the Amazon.com services. Asta Urbanaviciute (Self-publishing of Lithuanian cultural periodicals in Soviet and contemporary times) compares self-publishing in historical and modern contexts, demonstrating that contemporary self-publishing emerged under favourable circumstances, and that modern self-publishers associate this model with digital texts only, which, due to favourable conditions, spread easily through social networks and blogs. A completely different, historical self-publishing could have had serious political consequences, as summarized in the Russian description “I write it myself, censor myself, publish it myself and sit in jail myself”. Section two, models used in the digital environment, is comprised of three papers. Maja Krtalić and Damir Hasenay (Long-term accessibility of e-books: challenges, obstacles, responsibilities) ask how specific characteristics of e-books influence their preservation possibilities and who is responsible for the long-term accessibility of e-books? They concentrate on issues concerning the preservation and archiving of published authors’ works in the digital environment for the purpose of their long-term accessibility, and give an overview of relevant legal, technical, societal and organisational issues from which challenges, obstacles and responsibilities in ensuring long-term accessibility of e-books arise. Ivona Despot, Ivana Ljevak Lebeda and Nives Tomašević in the paper ’Freemium’ business models in publishing. New packaging for the needs of readers in the digital age explore how the emergence of subscription models influences the development of new publishing products which bring together the author and the publisher in a joint effort to reach a larger number of readers; and Ivana Hebrang Grgić (Publishing Croatian scientific journals: to e- or not to e-?) discusses the extent to which Croatian journal publishers adapted to the electronic environment. In section three, dedicated to the teaching of publishing at the university level, Aušra Navickienė (Third Level Publishing Studies: Lithuania, a Case Study), Ewa Jabłońska-Stefanowicz (Three R’s in publishing education), and Josipa Selthofer (What comes first? Publishing business or publishing studies?) provide examples of publishing studies programmes in Lithuania (focusing on the Institute of Book Science and Documentation of Vilnius University), Poland (focusing on the LIS Institute of the University of Wroclaw) and Croatia, in comparison with relevant programmes in Europe and the United States. Finally, section four presents three papers which petition for the status of publishing studies as an emerging scientific discipline. Sophie Noël in Publishing studies: the search for an elusive academic object questions the validity of publishing studies as an academic discipline, while trying to situate them within the field of social sciences. She argues that a more appropriate frame could be adopted to describe what people studying the transformations of book publishing do – or should do – both at a theoretical and methodological levels. Christoph Bläsi (Publishing studies: being part of a cultural practice plus x?) relates the question of an advanced self-conception of publishing studies to the question what criteria have to be fulfilled to call a field (such as publishing studies) a scholarly discipline. He presents the first results of an ongoing project in which he conducts extensive expert interviews with representatives of UK Publishing Studies study programmes and research institutions and, based on the interviews, defines the core questions related to publishing studies as a discipline. To finish, Bertrand Legendre (Publishing studies: what else?) tries to reposition publishing studies in the long process that starts with the beginning of book history and goes all the way to the current research on cultural industries. Overall, all the papers are concerned with new developments at the publishing scene, regarding its practical components, its educational scope, and its academic foundations. They reflect the general state of affairs in the comparably still very young scholarly discipline, which, since the late 1980ies, has been getting more and more attention both as research and teaching. In the last decade a number of significant monographs and scholarly papers have appeared, a few international conferences have addressed this topic, and more universities have included publishing courses. Yet, we still cannot say that today’s publishing studies are theoretically and methodologically mature enough to contextualize and analyse all the phenomena and developments in modern publishing, neither have we answered the questions such as what publishing studies are and what is their focus. Papers published in this volume of Libellarium could be taken as a contribution in building a general theoretical framework and methodological approaches that would fit publishing studies research best, and as attempts to answer the simple questions about the nature of the discipline and the background of scholars involved with it.